Citra Merek dan Keputusan Pengguna Grab Bike di Era New Normal pada Generasi Z di Kota Palembang - Resika, Yeri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is aimed at finding out the effect of brand image on the decisions of Grab Bike users in Palembang City. The research was conducted on Sekolah Tinggi Ilmu Ekonomi (STIE) APRIN Palembang students. Quantitative research is the type of research used and the research technique used, namely the technique of collecting research data with a questionnaire using a Likert scale. The research was conducted on Grab Bike users with a total of 79 respondents. Samples were taken using a non-probability sampling method, the snowball sampling method was chosen. The research data analysis method is linear regression. The results obtained from this research will be used to enrich knowledge about marketing research. Based on the results obtained, namely the indicators of the research variables, they are valid and reliable. The result of the coefficient of determination (R²) is 0.301 or 30.1%, which explains that the relationship of variable X to variable Y is positive but not significant. Brand image can explain purchasing decisions by 30.1%, while 60.9% is explained by other factors not included in this study. Simple linear regression testing shows that the regression coefficient of the brand image variable is 0.432 with a positive value, which means that every time there is an increase in the brand image by one point and other variables have a fixed value, the user's decision will increase by 0.432 units. The constant value of 3,976 indicates that when a company has a good brand image, the value of user decisions about Grab services will increase.